The Korean War in Britain : citizenship, selfhood and forgetting - Huxford, Grace (Cultural history of modern war., 2018)
The Korean War in Britain is the first social history of the Korean War (1950-1953) in Britain. Assessing the impact of the war from 1950 to the early twenty-first century, this original book examines how British people responded to the Korean War and it came to be known as the 'Forgotten War' of the twentieth century.